2015
DOI: 10.17772/gp/58640
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between colposcopy results using the Reid Colposcopic Index and histopathology

Abstract: Objectives: The aim of the study was to evaluate the diagnostic efficacy of colposcopy and to determine the strength of correlation between colposcopic impression using the Reid Colposcopic Index (RCI) and histopathology. Material and methods:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Further calculations of significant differences confirmed the superiority. In various reports over the past 30 years, the sensitivity, specificity, PPV, and NPV of the RCI were shown to be extremely variable [ 1 , 19 – 21 , 25 , 26 ], while the results of the modified RCI and Swede Score were roughly equal to ours [ 2 , 3 , 8 , 9 , 22 , 23 ]. A few studies have reported the colposcopic accuracy of the IFCPC classification.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Further calculations of significant differences confirmed the superiority. In various reports over the past 30 years, the sensitivity, specificity, PPV, and NPV of the RCI were shown to be extremely variable [ 1 , 19 – 21 , 25 , 26 ], while the results of the modified RCI and Swede Score were roughly equal to ours [ 2 , 3 , 8 , 9 , 22 , 23 ]. A few studies have reported the colposcopic accuracy of the IFCPC classification.…”
Section: Discussionmentioning
confidence: 64%
“…As the most well-known scoring system, the RCI was first reported by Reid and Scalzi in 1985 [1] and was shown to have good consistency of strength kappa as 0.55–0.74 with histopathology in several reports [19–21, 25, 26]. However, with cervical screenings and typical colposcopic impressions of precancers becoming increasingly uncommon, the accuracy of colposcopy as the standard method has been questioned [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RCI is one of the most verified colposcopic scoring system for evaluating the precancerous cervical lesions. According to the previous studies investigating correlation of RCI and CIN lesions, there was good correlation between RCI and histopathology [1516]. It consists of 4 colposcopic signs including color, vessels, margin, and iodine staging, and each sign is assigned between 0 and 2 according to colposcopic findings.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason is lack of effective screening programmes which can detect and treat preliminary stage of this life threatening disease [3]. Cervical cancer has a long latent phase and can be easily prevented using early screening methods, including Pap smears, human papilloma virus (HPV) testing, cervical examination using acetic acid, Lugol's iodine and colposcopy [4,5].…”
Section: Introductionmentioning
confidence: 99%